Epidermólise bolhosa: um desafio para a (sobre) vida - Prazeres, Silvana Mara Janning (Universidade do Vale do Rio dos Sinos, 2016)
The Epidermolysis Bullosa (EB) is a hereditary genodermatosis. In other words, it is a genetically transmitted skin disease. It’s a rare disease, which is characterized by the manifestation of blisters, ulcerations or wounds anywhere on the body surface either in response to the smallest traumas or spontaneously triggered. The objectives of this study were the elaboration of a practical guide for the handling of newborn babies who are of Epidermolysis Bullosa (EB); investigate how health professionals who work in neonatal intensive care units (ICUs) face the birth and the necessary care of newborn EB carriers, aiming to support the elaboration of the practical guide. This study has a qualitative, exploratory and descriptive nature and it was carried out in health institutions, which have already had cases of the disease in ICUs in the city of Porto Alegre/RS. The research followed the 466/12 resolution of the National Health Council. The project was approved by the UNISINOS Ethical and Research Committee (technical opinion 780.693 on September 8th 2014) and by the coparticipating institutions (technical opinions 837.816 on September 9th 2014 and 14171 on October 22nd 2014) Ethical and Research Committees. A total of 14 health professionals who had taken care of newborns with EB during their trajectory participated in this research. Eight of them are nurses, plus three nurse technicians and three physicians. The data collection was carried out by in-depth interviews, composed by two open questions: describe your experience concerning the care, treatment and monitoring of EB patients who are or have been under your care during hospitalization. And they were asked to tell what it was like to them. The data analysis was constituted by thematic analysis. This resulted in three categories: care experimentation, family and health team. The results indicated that the birth of an EB child leads to suffering due to the insecurity in terms of handling the case as much as to the gravity of the disease and its confrontation during the lives of the assisted patient and their family members. It is considered that the elaboration of this guide can support the assistance of EB newborns, contributing to the care qualification, including in-hospital assistance, and to a better home care orientation to the children’s parents.
Keywords: Epidermólise bolhosa; Cuidados de enfermagem; Recém-nascido; Epidermolysis bullosa; Nursing care; Infant Newborn; ACCNPQ::Ciências da Saúde::Enfermagem